Regulatory Mechanisms of Phenolic Acids in Metabolic Dysfunction-Associated Steatotic Liver Disease: A Review - Shengyu Zhang; Congcong Shen; Han Di; Yanhong Wang; Feng Guan (Antioxidants)
Metabolic dysfunction-associated steatotic liver disease (MASLD), the leading chronic liver condition globally, constitutes a major etiological contributor to hepatocellular carcinoma (HCC). Its transition from steatosis to non-alcoholic steatohepatitis (NASH) involves progressive fibrosis, ultimately predisposing to HCC. The pathogenesis involves multifactorial interactions among genetic susceptibility, environmental triggers, and obesity-associated metabolic dysregulation. Crucially, the gut–liver axis serves as a pivotal regulatory mechanism in MASLD development. Current therapeutic strategies prioritize lifestyle interventions for metabolic syndrome management, while pharmacological options remain limited, underscoring the need for new therapies. Emerging evidence highlights phenolic acids—bioactive phytochemicals from medicinal plants—as multi-target agents against MASLD. These compounds demonstrate therapeutic efficacy via antioxidative modulation of stress, anti-inflammatory activity, and gut–liver axis regulation. This review synthesizes recent advances in natural phenolic acids for MASLD intervention, emphasizing their potential as preventive and therapeutic candidates. Their multimodal mechanisms may inform innovative drug development paradigms targeting MASLD pathogenesis.